The Rule of Law and the Principle of Equality Before the Law: Theory and Its Manifestation in Indonesia - Marzuki, Ismail (MIH FH UNSOED, 2024)
The rule of law and the principle of equality before the law require the lives of the nation and state without arbitrariness and discrimination. The state constitution should provide protection to citizens; in judicial practice, it turns out that not a few justice seekers, especially ordinary people, find injustice. The purpose of this research is to examine the concept of the rule of law and the principle of equality before the law philosophically, and what its manifestations are in Indonesia. This study uses a normative juridical method with a legislative approach and a conceptual approach. The results show that the rule of law talks about